FREEDOM OF SPEECH AND THE PANDEMIC - Noor Farihah Mohd Noor , (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Freedom of speech has always been debated as critical. A lot of people misconceived them as total rights which permits them to exercise them without limitations. Many have exceeded the limit by expressing themselves inappropriately. Freedom of speech is important to maintain human dignity. But some quarters have misunderstood it so much so that this right has been distorted and deformed to suit some private agenda. There has been prosecution made under the anti-fake news law relating to the dissemination of Covid 19 news to instil panic in the people. This paper is important as it provides some insights on how laws are made to restrict freedom and how such rights should be exercised with responsibility and accountability to bring about overall peace and harmony.